2012
DOI: 10.1007/s10549-012-2382-0
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of circulating tumor cells in subtypes of metastatic breast cancer

Abstract: The detection of circulating tumor cells (CTCs) in the peripheral blood of metastatic breast cancer (MBC) patients is an independent marker of prognosis. This large prospective multicenter study aimed to assess the impact of CTCs on overall survival (OS) and progression free survival (PFS) in patients with predefined molecular subgroups of MBC. To this end, 468 MBC patients were divided into three subgroups based on immunohistochemical staining of the primary tumor: (1) hormone receptor-positive/HER2-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 24 publications
3
72
0
4
Order By: Relevance
“…In a larger study, 468 MBC patients were divided into three subgroups based on immunohistochemical staining of the primary tumor: hormone receptor postive, Her2-positive and triple negative groups. This study confirmed independent prognostic value of CTC detection but lack to show difference between primary tumor-based molecular subgroups and impact of CTC status on survival (Wallwiener et al, 2013). Circulating cell-free DNA carrying tumor-specific alterations (circulating tumor DNA) has been investigated and compared with cancer antigen 15-3 (CA 15-3) and circulating tumor cells in a recent study (Dawson et, al., 2013).…”
Section: Introductionsupporting
confidence: 70%
“…In a larger study, 468 MBC patients were divided into three subgroups based on immunohistochemical staining of the primary tumor: hormone receptor postive, Her2-positive and triple negative groups. This study confirmed independent prognostic value of CTC detection but lack to show difference between primary tumor-based molecular subgroups and impact of CTC status on survival (Wallwiener et al, 2013). Circulating cell-free DNA carrying tumor-specific alterations (circulating tumor DNA) has been investigated and compared with cancer antigen 15-3 (CA 15-3) and circulating tumor cells in a recent study (Dawson et, al., 2013).…”
Section: Introductionsupporting
confidence: 70%
“…Numerous published studies demonstrate that CTC prevalence predicts disease recurrence and survival in patients with metastatic breast cancer (MBC; refs. [2][3][4][5][6], and the persistence of CTCs after treatment has been shown to predict lack of responses to therapy in metastatic settings (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] The prognostic value of this cutoff value has been further verified by several studies and still in utilization. [21,22] Besides the prognostic role of CTC status, alteration in CTC levels during treatment has also been shown to reflect therapy response in metastatic BC. The study of Hayes et al indicated that, a decrease in CTC levels under the threshold of five-cells/7.5 ml PB predicted better PFS and OS in metastatic BC.…”
Section: Ctc Detection Methodsmentioning
confidence: 99%
“…The dynamic individual mutations can be detected by using former approach, but it requires of specific CTC types on patient survival have contradictory results. For example, while one study determined that patients with HER2-positive CTCs had significantly longer PFS, [22] another study showed that patients with HER2-positive CTCs had significantly worse survival; [25] and another study determined that HER2 status of CTCs in metastatic BC had no correlation with clinical outcome. [26] An ongoing clinical trial called DETECT may provide results to resolve this enigma.…”
Section: Ctc Detection Methodsmentioning
confidence: 99%